Drug-induced acute kidney injury: a cohort study on incidence, identification of pathophysiological mechanisms, and prognostic factors - Garcia, Georgia; Pacchini, Vinicius Repetti; Zamoner, Welder; Balbi, Andre Luis; Ponce, Daniela (Frontiers in Medicine, 2024)
Introduction: Acute Kidney Injury (AKI) is a common clinical syndrome. Drug-Induced Acute Kidney Injury (DI-AKI) is associated with exposure to nephrotoxic medications, particularly among hospitalized patients. Adverse drug reactions comprises type A (predictable based on the pharmacology of the substance, dosedependent) and type B (unpredictable, idiosyncratic, not dose-dependent) reactions. Objective: To evaluate DI-AKI incidence, identify the main associated drugs and the pathophysiological mechanism of the observed injury, analyze prognostic factors associated with unfavorable outcomes, and compare the outcomes of death and the need for Acute Kidney Support Therapy (AKST) between patients with DI-AKI vs. AKI due to other etiologies. Methods: A retrospective cohort study conducted at the Hospital das Clínicas of the Faculty of Medicine of Botucatu -UNESP (HC-FMB), using data from patients hospitalized between January 2016 and April 2022. Inclusion criteria: diagnosis of AKI and Chronic Kidney Disease (CKD) with superimposed AKI. Exclusion criteria: patients under 18 years old or on chronic Renal Replacement Therapy. AKI was diagnosed based on creatinine increase as established by KDIGO 2012. Data were presented as mean and standard deviation or median with interquartile range and frequency. Statistical significance was set at 5% (p < 0.05). Logistic regression was performed to identify factors associated with the need for AKST and death. Results: A total of 1398 patients were analyzed. The most prevalent etiology of AKI was Mixed Ischemic + Septic AKI (28%). DI-AKI was a significant cause of AKI (19.3%). Among patients with DI-AKI, the majority were not subjected to AKST and survived. DI-AKI showed lower severity and mortality compared to other AKI etiologies but had a similar need for AKST (26.3% vs. 35.4%, p < 0.05 and 31.8% vs. 36.8%, p > 0.05). Most nephrotoxic drugs caused type A reactions, with Vancomycin being the primary nephrotoxin. Although the mortality rate is lower among DI-AKIs compared to other AKI etiologies, the need for AKST was similar. Therefore, it is recommended that DI-AKI be recognized early to enable dose reduction or even drug suspension, depending on the type of reaction, to reduce healthcare costs and improve clinical outcomes for patients.